Designing Policies for the Empowerment of Older Adults Through Used Cooking Oil Management Within the Social Protection Framework - Suratna Suratna (Green Publisher Indonesia, 2026)
The increasing number of the elderly population in Indonesia demands a transformation of social protection policies that are not only protective, but also productive and sustainable. This research aims to formulate a policy design for the empowerment of the elderly through the management of used cooking oil in the framework of social protection based on collaborative governance. The research uses a qualitative approach with literature study methods and conceptual analysis of circular economy-based empowerment policies and practices. The results of the study show that the social protection policy of the elderly in Indonesia is still dominated by a charitable approach, so it has not been able to optimize the potential of the elderly as economic actors. On the other hand, used cooking oil management has significant economic and ecological potential, but has not been systematically integrated into policy design. The integration of these three dimensions allows for effective cross-sectoral collaboration between government, society, and the private sector. Therefore, this study recommends the transformation of the role of the government, especially the Ministry of Social Affairs, as a metagovernor who is able to orchestrate collaboration between actors in developing policies for the empowerment of the elderly based on the circular economy. This policy design is expected to improve the welfare of the elderly, strengthen social inclusion, and support sustainable development.